Simultaneous Optimization of Rigorous Reactor Design and Process Synthesis: Application to Direct CO2 Conversion of Methanol - HeWonLee; Lee, Ung; Na, Jong geol; Kim, Hong Gon (AiChE, 2019)
Although the direct methanol synthesis using CO2 hydrogenations has been recognized a promising option for both hydrogen storage and CO2 utilization, the hydrogen cost and extreme operating conditions of the direct CO2 conversion has been pointed out as an obstacle for the commercialization. In this study, we firstly propose an innovative reactor design of direct conversion of CO2 to methanol. The proposed reactor consists of multi-stages where each stage has unique characteristic space velocity, temperature, feed stream composition, and the amount of catalyst. A multi-scale model which can determine the number of stages, geometry, operating condition, and economic potential of the reactor is also developed. The multi-scale model simultaneously calculates computational fluid dynamics (CFD) and a process simulator in order to integrated continuum level information (i.e., the reaction kinetics, heat and mass transfer inside the reaction) with process level information such as number of stages, operating condition, and economic potential. we developed the multi-scale model to understand the reaction kinetics, heat and mass transfer inside the reaction via CFD and integrate the reactor information to techno-economic analysis via process simulation. The rigorous temperature profiles inside of the reactor of each tube was calculated by the shell and tube type multi-tubular packed bed reactor CFD model. These profiles were mapped to discretized Aspen Plus packed bed reactor model. After calculating the CFD model iteratively using the heat of reaction from Aspen Plus model, converged multi-scale model information can be obtained. The optimum multi-stage reactor shows better methanol yield than conventional isothermal reactor and also decrease total mole flow rate of entire process. Also, the optimized reactor design has improved equipment and operating cost thus the proposed design can be easily adopted for the real industrial application.